2022
DOI: 10.1111/ecog.05956
|View full text |Cite
|
Sign up to set email alerts
|

Understanding complex spatial dynamics from mechanistic models through spatio‐temporal point processes

Abstract: Landscape heterogeneity affects population dynamics, which determine species persistence, diversity and interactions. These relationships can be accurately represented by advanced spatially-explicit models (SEMs) allowing for high levels of detail and precision. However, such approaches are characterised by high computational complexity, high amount of data and memory requirements and spatio-temporal outputs may be difficult to analyse. A possibility to deal with this complexity is to aggregate outputs over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Aggregating outputs over space, however, may have masked local patterns and possible local peaks in pest densities. In a recent modelling study of a specialist pest and a generalist predator interacting in an heterogeneous agricultural landscape, Zamberletti et al (2021, 2022) showed for example that semi-natural habitats increased the average landscape scale pest density (by reducing the number of necessary pesticide treatments) but locally reduced peaks of pest populations(Zamberletti et al, 2021, 2022). Further analyses of pest density dynamics at the field level would, thus, be necessary to confirm the better ranking of the IP scenario regarding local CBC and pest densities.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregating outputs over space, however, may have masked local patterns and possible local peaks in pest densities. In a recent modelling study of a specialist pest and a generalist predator interacting in an heterogeneous agricultural landscape, Zamberletti et al (2021, 2022) showed for example that semi-natural habitats increased the average landscape scale pest density (by reducing the number of necessary pesticide treatments) but locally reduced peaks of pest populations(Zamberletti et al, 2021, 2022). Further analyses of pest density dynamics at the field level would, thus, be necessary to confirm the better ranking of the IP scenario regarding local CBC and pest densities.…”
Section: Discussionmentioning
confidence: 99%
“…Stage 3 identifies the causes of initial population declines and later extinctions. This is done by analysing simulation outputs from the 'best' SEPMs, using spatiotemporal statistical techniques that allow the role of environmental threats on change in occupancy and abundance to be disentangled spatiotemporally (Zamberletti et al, 2022).…”
Section: Model Development and Application Is Broken Into Three Stagesmentioning
confidence: 99%
“…Stage 3 identifies the causes of initial population declines and later extinctions. This is done by analysing simulation outputs from the ‘best’ SEPMs, using spatiotemporal statistical techniques that allow the role of environmental threats on change in occupancy and abundance to be disentangled spatiotemporally (Zamberletti et al, 2022). Causal explanations regarding the isolated or interactive effects of these threatening processes on emergent patterns can be further tested using counterfactual scenarios (Figure 4), whereby combinations of drivers of environmental change are switched off, while keeping all other parameters fixed (Fordham et al, 2021, 2022).…”
Section: Emerging Research Program In Conservation Biogeographymentioning
confidence: 99%
“…Aggregating outputs over space, however, may have masked local patterns and possible local peaks in pest densities. In a recent modelling study of a specialist pest and a generalist predator interacting in an heterogeneous agricultural landscape, Zamberletti et al (2021Zamberletti et al ( , 2022 showed for example that semi-natural habitats increased the average landscape scale pest density (by reducing the number of necessary pesticide treatments) but locally reduced peaks of pest populations (Zamberletti et al, 2021(Zamberletti et al, , 2022. Further analyses of pest density dynamics at the field level would, thus, be necessary to confirm the better ranking of the IP scenario regarding local CBC and pest densities.…”
Section: Limits and Benefits Of The Modelling Approachmentioning
confidence: 99%